2021
DOI: 10.5937/jomb0-26055
|View full text |Cite
|
Sign up to set email alerts
|

Workflow optimization in a clinical laboratory using Lean management principles in the pre-analytical phase

Abstract: BACKGROUND: The application of the Lean methodology in clinical laboratories can improve workflow and user satisfaction through the efficient delivery of analytical results. The purpose of this study was to optimise delivery times of the test results at a clinical laboratory, using Lean management principles in the pre-analytical phase. METHODS: A prospective study with a quasi- experimental design was implemented. Staff functions were restructured and sample flows were modified. Delivery times of clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
(16 reference statements)
0
6
0
1
Order By: Relevance
“…Each sample was prioritized based on patient characteristics (e.g., clinical case, health care worker, etc). However, this traditional approach can impact the productivity of the lab and cause prolonged turnaround times ( 15 17 ). To streamline the workflow, the workflow was visualized, and opportunities for improvement were identified ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Each sample was prioritized based on patient characteristics (e.g., clinical case, health care worker, etc). However, this traditional approach can impact the productivity of the lab and cause prolonged turnaround times ( 15 17 ). To streamline the workflow, the workflow was visualized, and opportunities for improvement were identified ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The study results are comparable with other studies, where a significant positive change in TAT was observed after initiating and implementing the Lean process throughout their laboratory. 2,5,6 However, the impact of the Lean Six Sigma on TAT was reduced due to the significant drop in the number of samples received post implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Staff resistance to change is one of the main barriers, along with lack of support from management and financial constraints. On the opposite side, Letelier [ 25 ] et al mentioned that results were achieved with minimum financial investment (except for the structural modifications). Another case study in a tertiary care pediatric hospital in Nova Scotia, Canada, did not require high financial or time investment, as mentioned by Geerlinks et al [ 31 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Letelier et al [ 25 ] mentioned that implementation contributed to the emergence of a culture of continuous improvement in the laboratory. Still, analyzing all the selected articles, we can conclude that too little emphasis was placed on the effects that Lean has on organizational culture and on improving relationships within work teams and focused only on quantitative performance measurement, specifically on the analysis of key performance indicators.…”
Section: Literature Reviewmentioning
confidence: 99%